EDUKASI PENGOLAHAN SAMPAH BOTOL PLASTIK MENJADI “POT” TANAMAN - Masnur, Masnur; Farid, Muhammad; Paramitha, Anggi; Absharillah, Andi Bidasari; Handayani, Putri; Ibrahim, Wulansari (Batara Wisnu : Indonesian Journal of Community Services, 2021)
Until now, the participation of the community, in general, is only limited to waste disposal, but it has not yet reached the stage of waste management that can be useful again for the community. Therefore, waste management can take the form of disposing of waste or returning waste into valuable materials. This activity aims to provide educative training on how to carry out reforestation in narrow areas and an effort to increase public awareness in dealing with plastic waste that continues to grow. The method used is to educate the orphanage children, explain and understand waste, impacts, 3R materials, and practice processing plastic bottles into "POTS." As a result of the essential nature of the training, the results achieved are pretty good, considering that making pots from used plastic bottles requires skill and perseverance from the participants